2009
DOI: 10.1096/fj.09-139519
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glial cells protect neurons from oxidative stress in partviareduced glutathione

Abstract: Enteric glial cells (EGCs) are essential in the control of gastrointestinal functions. Although lesions of EGCs are associated with neuronal degeneration in animal models, their direct neuroprotective role remains unknown. Therefore, the aims of this study were to demonstrate the direct neuroprotective effects of EGCs and to identify putative glial mediators involved. First, viral targeted ablation of EGCs in primary cultures of enteric nervous system increased neuronal death both under basal conditions and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 40 publications
5
86
0
1
Order By: Relevance
“…The functional consequences of this infection and whether or not the infected glia will go on to die remain to be determined. These findings are consistent with previous work showing that the enteric glia are preferentially infected with adenovirus in vitro (40) and suggest that viral infection of glia may lead to dysfunction and contribute to dysmotility.…”
Section: Role Of Enteric Glia In Gi Motility Disorderssupporting
confidence: 93%
“…The functional consequences of this infection and whether or not the infected glia will go on to die remain to be determined. These findings are consistent with previous work showing that the enteric glia are preferentially infected with adenovirus in vitro (40) and suggest that viral infection of glia may lead to dysfunction and contribute to dysmotility.…”
Section: Role Of Enteric Glia In Gi Motility Disorderssupporting
confidence: 93%
“…22 In neuron-glia co-cultures in vitro, the story is clearer and Abdo et al identified reduced glutathione and 15d-PGJ2 as factors secreted by enteric glial cells that protect neurons from oxidative stress. 71,72 Glial cell line-derived neurotrophic factor (GDNF) is also a prospective enteric glial-derived neuroprotective factor, 73 but the physiological significance of GDNF secretion by enteric glia is unclear. Transgenic overexpression of GDNF in glia was necessary for neuroprotective effects, 73 and GDNF expression is normally confined to smooth muscle cells and not enteric glia.…”
Section: Neurogenesis and Neuron Survivalmentioning
confidence: 99%
“…This suggests that EGCs are involved in the survival of enteric neurons. Furthermore, this study also showed that neuronal susceptibility to damaging factors such as oxidative stress (H 2 O 2 or dopamine) was enhanced as a result of EGC loss (1). Concerning soluble factors released by EGCs, in vitro and ex vivo data have demonstrated that reduced glutathione (GSH), but not oxidized glutathione or S-nitrosoglutathione, can prevent enteric neuronal cell death induced by H 2 O 2 .…”
Section: Egc Neuroprotective Functions: Lessons From Enteric Glia Ablmentioning
confidence: 70%
“…Concerning soluble factors released by EGCs, in vitro and ex vivo data have demonstrated that reduced glutathione (GSH), but not oxidized glutathione or S-nitrosoglutathione, can prevent enteric neuronal cell death induced by H 2 O 2 . Selective genetic inhibition of glutamate cysteine ligase (the key enzyme of glutathione synthesis) in EGCs increased neuronal susceptibility to death induced by oxidative stress (1,40). Furthermore, EGC protective effects could also be due to their detoxification properties since they are able to take up glutamate or ␥-aminobutyric acid from an extracellular milieu by means of L-glutamate transporter (42) or ␥-aminobutyric acid transporter 2 (19), respectively.…”
Section: Egc Neuroprotective Functions: Lessons From Enteric Glia Ablmentioning
confidence: 99%